Human Stem Cell-Derived Neurospheroids and a Multi-Assay Strategy Provide Brain Cytotoxicity New Insights from ADB-FUBIATA Exposure - Uliana De Simone; Carlo Alessandro Locatelli; Francesca Caloni; Davide Lonati; Luciana Alessandra Russo; Teresa Coccini (Neurotoxicity Research, 2026)

Cocoa bean shells as a source of functional fiber in a muffin model - Margherita Stampini; Vincenzo Disca; Francesca Carrà; Sara Scardino; Gianluca Piana; Fabiano Travaglia; Jean Daniel Coïsson; Monica Locatelli; Marco Arlorio (Food Chemistry, 2026)

From paddy to polished rice: investigating antioxidant activity and phenolic compounds in Italian conventional and pigmented rice varieties and their by-products - Yassine Jaouhari; Debora Giordano; Fabiano Travaglia; Claudia Sardella; Francesca Vanara; Jean Daniel Coisson; Marco Arlorio; Monica Locatelli; Massimo Blandino (Food Chemistry, 2025)

Treatments of food and food by-products to enhance gut microbiota short-chain fatty acids production - Vincenzo Disca; Francesca Carrà; Margherita Stampini; Marco Arlorio; Monica Locatelli (Food Bioscience, 2025)

Association between long-term exposure to air pollution and cause-specific mortality within five Italian longitudinal metropolitan studies - Federica Nobile; Nicola Caranci; Elena Strippoli; Valentina Adorno; Alessandra Allotta; Lucia Bisceglia; Ida Galise; Claudio Gariazzo; Sara Maio; Paola Michelozzi; Walter Pollina Addario; Andrea Ranzi; et al. (Atmospheric Environment, 2024)

Residential exposure to air pollution and incidence of leukaemia in the industrial area of Viadana, Northern Italy - Francesca Locatelli; Luigi Martinelli; Pierpaolo Marchetti; Gulser Caliskan; Chiara Badaloni; Nicola Caranci; Kees de Hoogh; Luciana Gatti; Paolo Giorgi Rossi; Linda Guarda; Marta Ottone; Silvia Panunzi; et al. (Environmental Research, 2024)

Long-term residential exposure to air pollution and risk of chronic respiratory diseases in Italy: The BIGEPI study - Pierpaolo Marchetti; Jessica Miotti; Francesca Locatelli; Leonardo Antonicelli; Sandra Baldacci; Salvatore Battaglia; Roberto Bono; Angelo Corsico; Claudio Gariazzo; Sara Maio; Nicola Murgia; Pietro Pirina; et al. (Science of The Total Environment, 2023)

Residential exposure to air pollution and adverse respiratory and allergic outcomes in children and adolescents living in a chipboard industrial area of Northern Italy - Silvia Panunzi; Pierpaolo Marchetti; Massimo Stafoggia; Chiara Badaloni; Nicola Caranci; Kees de Hoogh; Paolo Giorgi Rossi; Linda Guarda; Francesca Locatelli; Marta Ottone; Caterina Silocchi; Paolo Ricci; et al. (Science of The Total Environment, 2023)

Pulse type and extrusion conditions affect phenolic profile and physical properties of extruded products - Massimo Blandino; Andrea Bresciani; Monica Locatelli; Mattia Loscalzo; Fabiano Travaglia; Francesca Vanara; Alessandra Marti (Food Chemistry, 2023)

Effect of enrichment of rice snacks with pulse seed coats on phenolic compound content, product features and consumer hedonic response - Andrea Bresciani; Francesca Vanara; Ella Pagliarini; Monica Locatelli; Cristina Proserpio; Fabiano Travaglia; Massimo Blandino; Alessandra Marti (Food Chemistry, 2023)

Association between short-term exposure to air pollutants and cause-specific daily mortality in Italy. A nationwide analysis - Claudio Gariazzo; Matteo Renzi; Alessandro Marinaccio; Paola Michelozzi; Stefania Massari; Camillo Silibello; Giuseppe Carlino; Paolo Giorgi Rossi; Sara Maio; Giovanni Viegi; Massimo Stafoggia; Sandra Baldacci; et al. (Environmental Research, 2023)

Spatial variability of nitrogen dioxide and formaldehyde and residential exposure of children in the industrial area of Viadana, Northern Italy - Alessandro Marcon; Silvia Panunzi; Massimo Stafoggia; Chiara Badaloni; Kees de Hoogh; Linda Guarda; Francesca Locatelli; Caterina Silocchi; Paolo Ricci; Pierpaolo Marchetti (Environmental Science and Pollution Research, 2021)
Chipboard production is a source of ambient air pollution. We assessed the spatial variability of outdoor pollutants and residential exposure of children living in proximity to the largest chipboard industry in Italy and evaluated the reliability of exposure estimates obtained from a number of available models. We obtained passive sampling data on NO 2 and formaldehyde collected by the Environmental Protection Agency of Lombardy region at 25 sites in the municipality of Viadana during 10 weeks (2017–2018) and compared NO 2 measurements with average weekly concentrations from continuous monitors. We compared interpolated NO 2 and formaldehyde surfaces with previous maps for 2010. We assessed the relationship between residential proximity to the industry and pollutant exposures assigned using these maps, as well as other available countrywide/continental models based on routine data on NO 2 , PM 10 , and PM 2.5 . The correlation between NO 2 concentrations from continuous and passive sampling was high (Pearson’s r = 0.89), although passive sampling underestimated NO 2 especially during winter. For both 2010 and 2017–2018, we observed higher NO 2 and formaldehyde concentrations in the south of Viadana, with hot-spots in proximity to the industry. PM 10 and PM 2.5 exposures were higher for children at < 1 km compared to the children living at > 3.5 km to the industry, whereas NO 2 exposure was higher at 1–1.7 km to the industry. Road and population densities were also higher close to the industry. Findings from a variety of exposure models suggest that children living in proximity to the chipboard industry in Viadana are more exposed to air pollution and that exposure gradients are relatively stable over time.

The role of the thymus in allogeneic bone marrow transplantation and the recovery of the peripheral T-cell compartment - Enrico Velardi; Emmanuel Clave; Lucas C. M. Arruda; Francesca Benini; Franco Locatelli; Antoine Toubert (Seminars in Immunopathology, 2021)

Case series: paradoxical action of domperidone leads to increased vomiting - Marco Pozzi; Sandra Strazzer; Federica Locatelli; Sara Galbiati; Francesca Formica; Luciano Maestri; Emilio Clementi; Sonia Radice (European Journal of Clinical Pharmacology, 2013)

Different molecular mechanisms causing 9p21 deletions in acute lymphoblastic leukemia of childhood - Francesca Novara; Silvana Beri; Maria Ester Bernardo; Riccardo Bellazzi; Alberto Malovini; Roberto Ciccone; Angela Maria Cometa; Franco Locatelli; Roberto Giorda; Orsetta Zuffardi (Human Genetics, 2009)

Characterisation of gastric ghrelin cells in man and other mammals: studies in adult and fetal tissues - Guido Rindi; Vittorio Necchi; Antonella Savio; Antonio Torsello; Michele Zoli; Vittorio Locatelli; Francesca Raimondo; Daniela Cocchi; Enrico Solcia (Histochemistry and Cell Biology, 2002)